Comparison of dose measurements in CT using a photodiode and a small ion chamber. (August 2016) - Paschoal, C.M.M.; Ferreira, F.C.L.; Souza, D.N.; Santos, L.A.P.
Abstract: Owing to the advance of multislice computed tomography (CT), the dosimetric protocol currently used in CT has become inadequate. Instead of dosimetry based on the measurement of the Computed Tomography Dosimetry Index (CTDI) using a pencil ion chamber (IC) 100 mm in length, the use of a short IC and the calculation of the dose equilibrium (Deq ) at the location of the chamber are proposed. The objective of this work was to compare the performance of a short IC and a commercial photodiode (BPW34FS) to measure the accumulated dose at the center of the scan length L, DL (0), and to obtain the equilibrium dose Deq using the two detectors. The result for L = 100 mm was compared with the result of the pencil chamber. The results indicate that the commercial photodiode is suitable to measure the accumulated dose at the center of the scan length L as compared with the ICs. This methodology allows measurements of the accumulated dose for any desired scan length, allowing measurement of the equilibrium dose Deq if the phantom is long enough to allow it. Highlights: CT beams have become larger and the dosimetric protocol has shown to be inadequate. Electronic semiconductor devices have some advantages for dosimetry applications. Dosimetric comparison between a short IC and a commercial photodiode was performed. Photodiode is suitable to measure the accumulated dose in CT beams.